Occupational Therapy and assistive technology: thoughts about the experience with collaborative school consulting - Baleotti, Luciana Ramos [UNESP]; Zafani, Mariana Dutra [UNESP] (Cuba Editora, 2017)
This study presents thoughts and ideas based on the experience developed in the project entitled Assistive Technology for Inclusion of Students with Physical Disorders: Resources and Procedures, in development since 2009. This project aims to help in the process of school inclusion of students with physical disorder in Early Childhood Education in the city of Marilia, Brazil, through the collaboration between Health and Education departments. Health professionals contribute through the implementation of the Assistive Technology by means of school consulting. The project has been developed in six different stages, namely: Gaining access and establishing goals for the team; Identifying the problem; Interventions/Recommendations; Implementation; Evaluation and further actions. This working model, seeks to insert occupational therapy in the school environment. This project showed the importance of occupational therapists as team members in school settings, and the importance of a collaborative work between Education and Health departments.
Keywords: Occupational Therapy; Assistive Technology; Physical Disability; Environment